Analysis of iPWR SMR behavior during malfunction events - Kaisas , Ioannis; Krezas, Georgios (HNPS Advances in Nuclear Physics, 2026)
Small modular reactors are nuclear reactors with a maximum power capacity of 300 MWe according to IAEA’s classification of nuclear reactors. Advertised for their short installation time, compared to traditional Nuclear Power Plants, and their negligible CO2 emissions, SMRs can act as a complementary power source to a renewable and carbon–free energy production power grid. Due to their low power and their passive safety systems, in case of operation failure, damage is minimized without human intervention. The shut down systems rely on physical phenomena to operate and minimize the risk of radioactivity release. For example, the passive decay heat removal system (PDHR) relies on natural circulation of the coolant, while the gravity driven water injection system (GIS) and the control rod actuation in case of SCRAM event rely on gravity. This study exploits IAEA’s iPWR simulation to observe the behavior of an SMR during different malfunction events. During malfunction events, different safety systems, such as the PDHR and GIS, are activated, as well as other safety systems such as the automatic depressurization system (ADS) and the pressure injection system (PIS), to prevent further damage. The malfunction events studied are turbine malfunction, loss of feedwater-flow, steam-line break inside containment building, and station blackout. In these scenarios, phenomena such as Xe build-up and decay heat from fission products after shutdown are analyzed. For example, in the loss of feedwater-flow malfunction, Xe reactivity reaches its most negative value of -3445 pcm after approximately 7 hours, while the average coolant temperature stabilizes at 155.5oC after 16 hours. Such results are valuable for the appropriate selection of materials and components of SMRs. Also, this study suggest an improvement in the given SMR design in the blackout malfunction event, in which the SMR cannot cool down properly since the ADS valves are “fail-close” valves and cannot depressurize the system, halting the operation of other safety systems. With suggestion of the "fail-open” design of these valves, this problem could be solved and further damage would be prevented.